Repair of abdominal aortic aneurysms: preoperative imaging and evaluation - Hu, David K.; Pisimisis, George T.; Sheth, Rahul A. (Cardiovascular Diagnosis and Therapy; Vol 8, Supplement 1 (April 13, 2018): Cardiovascular Diagnosis and Therapy (Advanced aortic imaging and intervention), 2018)
Imaging is a critical component of the pre-procedure evaluation and planning of endovascular aneurysm repair (EVAR). Imaging is the mainstay for proper assessment of procedural candidacy, relevant vascular anatomy, device selection, and surgical approach. Computed tomography angiography (CTA) has long been considered the preferred modality for pre-operative imaging and evaluation prior to EVAR. Recently, advances in image quality and software technology have further enhanced the proceduralist’s ability to plan and perform EVAR. In this review, we highlight the current state of the art to provide interventionalists a contemporary assessment of the available tools for pre-operative imaging and evaluation prior to EVAR.